ETNOGRAFI ASTROLOGI DAKWAH ISLAM KEPULAUAN DI KESULTANAN TIDORE - Syarifudin Syarifudin (Hikmah, 2018)
ABSTRACT; This research is concerned with Islamic islamic astrology. This research problem focused on the identification of Islamic archipelagic astrology by mengintragasikan with modern astrology in Tidore Sultanate as a contribution of healthy social change in the community. This research is characterized by phenomenology with ethnography approach. The problem of this research is how the integration of modern astrology and astrology in the Tidore sultanate. Data collection technique using medate deep interview Densin, Data analysis technique using Haberman and Miles model with display data, data reduction and conclusion. This study uses a multiparadigm approach in looking at social reality. This study found there are 9 types of black magic in the tradition of society if there is social conflict, this black magic media as a disturbing social life that ends in the death of the soul. In addition there are 14 white sciences that have a major contribution to maintaining the physical and spiritual health of Islamic islands in the city of Tidore. The role of Islamic astrology of this archipelago strongly influences the style of thinking of society in the process of cultural development and contributes in three aspects; 1). Astronomy all aspects of life to determine the day to achieve success in work, 2). Determining good days for political, cultural, and economic activities. Islamic astrology, especially for the people, mostly calls the elderly astrology rather than using modern ways of thinking on the aspects of death, body bath, house entry, weddings, and the determination of good days and even heavily influences the political color. 3). Islamic astrology is used as a guide to the healing process of medical and non medical diseases. Modern astrology is materialism Islamic astrology of islands is spirituality. The contribution of this study is to open an integrated scientific insight, interconnect with multiparadigm insight to formulate academic manuscripts of Islamic astrology of the archipelago as a contribution to the development of science.Key Word; Astrology, Islam, and the archipelago. ABSTRAC; Penelitian ini berkaitan dengan ilmu astrologi Islam kepulauan. Masalah penelitian ini terfokus pada identifikasi ilmu astrologi Islam kepulauan dengan mengintragasikan dengan astrologi modern di Kesultanan Tidore sebagai kontribusi perubahan sosial yang sehat di tengah masyarakat. Penelitian ini bercorak fenomenologi dengan pendekatan etnografi. Masalah penelitian ini adalah bagaimana Integrasi astrologi modern dan astrologi di kesultanan Tidore. Teknik pengumpulan data menggunakan medote deep interview Densin, Teknik analisis data menggunakan model Haberman dan Miles dengan melakukan display data, reduksi data dan kesimpulan. Kajian ini menggunakan pendekatan multiparadigma dalam mencermati realitas sosial. Penelitian ini menemukan ada 9 jenis ilmu hitam dalam tradisi masyarakat jika terjadi konflik sosial, media ilmu hitam ini sebagai pengganggu kehidupan sosial bermasyarakat yang berakhir pada kematian jiwa. Selain itu ada 14 ilmu putih yang memiliki kontribusi besar menjaga kesehatan jasmani dan rohani masyarakat Islam kepulauan di kota Tidore. Peran astrologi Islam kepulauan ini sangat memengaruhi corak berpikir masyarakat dalam proses pembangunan kebudayaan dan berkontribusi dalam tiga aspek; 1). Ilmu perbintangan semua aspek kehidupan untuk menentukan hari untuk mencapai kesuksesan dalam bekerja, 2). Menentukan hari-hari baik untuk melakukan aktivitas politik, budaya, dan ekonomi. Astrologi Islam khususnya bagi masyarakat lebih banyak mengutakan ilmu perbintangan orang tua-tua dari pada menggunakan cara berpikir orang modern pada aspek kematian, mandi jenazah, masuk rumah, acara pernikahan, dan penentuan hari baik dan bahkan ia sangat memengaruhi warna politik. 3). Astrologi Islam digunakan sebagai petunjuk untuk proses penyembuhan penyakit medis dan non medis. Astrologi modern bersifat materialism Astrologi Islam kepulauan bersifat spiritualialitas. Kontribusi kajian ini untuk membuka wawasan keilmuan yang terintegrasi, interkoneksi dengan wawasan multiparadigma untuk merumuskan naskah akademik Astrologi Islam kepulauan sebagai kontribusi pengembangan ilmu pengetahuan.Key Word; Astrologi, Islam, dan  kepulauan.